ROLLER COMPACTED CONCRETE RCC UNTUK BANGUNAN BENDUNGAN - Ruslan Djajadi; Deddy Hardianto; Henry James; Handoko Sugiharto (Institute of Research and Community Outreach - Petra Christian University, 2003)
The using of Roller Compacted Concrete (RCC) is one of many alternatives that can be used to decrease dam construction cost. Many Roller Compacted Concrete (RCC) composition has been developed to achieve maximum compressive strength. Due to the economical consideration and the possibility of the execution, drop hammer system has been used for this research. Compression test is done after the age of the sample reaches seven, 28, 60, and 90 days. The result shows that 60/40 composition of gravel/sand has higher average compressive strength on all age of sample. The highest compressive strength the achieve is 17.78 MPa for 90 days sample. Abstract in Bahasa Indonesia : Penggunaan Roller Compacted Concrete (RCC) merupakan salah satu alternatif yang dapat digunakan untuk mengurangi biaya pembuatan konstruksi bendungan. Berbagai komposisi benda uji Roller Compacted Concrete (RCC) dibuat untuk mengetahui kuat tekan yang paling maksimal. Ditinjau dari segi ekonomis dan kemudahan pelaksanaan, maka digunakan sistem alat pemadat drop hammer. Dilakukan tes kuat tekan setelah umur benda uji masing-masing mencapai tujuh, 28, 60, dan 90 hari. Hasil penelitian menunjukkan bahwa komposisi kerikil/pasir sebesar 60/40 selalu memiliki kuat tekan rata-rata yang lebih tinggi pada semua umur benda uji. Kuat tekan terbesar pada benda uji umur 90 hari mencapai 17.78 MPa.